Metro station evacuation safety assessment considering emergency response. (October 2022) - Li, Haiquan; Wang, Yan; Jiang, Juncheng; Zhou, Ru
The emergency response process will not start immediately in the initial stage of a subway accident, and information will not fully spread temporarily. Crowds in different regions receive different comprehensiveness of accident information. They will start evacuating at different times and at different desired speed states. Depending on this phenomenon, pedestrians were classified in simulation modeling. In addition, the different states of emergency gates, escalators, and automatic gate machines before and after the emergency response instruction were set up in the simulation. The impact of different emergency response times on evacuations was studied. The emergency response in advance did not make a significant promotion to evacuation efficiency, but delayed emergency response reduced it greatly. This work proposed an evacuation risk index (ERI) and maximum safe evacuation capacity in metro stations. The worst accident evacuation scenario can be obtained by calculating the ERI, and a metro station was evaluated as a case study. The comparison of the evaluation results of ERI and other methods shows that the conclusion is consistent, but ERI considers the accident location factor.